ANALISIS KONSEPTUAL: PARADOKS KELANGKAAN DAN ESKALASI HARGA BBM TERHADAP STABILITAS INDEKS HARGA KONSUMEN - Siti Mey Listianti; Eva Indriyani; M Faris Abrar; Nazla Davini; Nasywa Maulidia; Teguh Adzuri; Silvia Asti Indriani; Laila Asifa Walidati; Novia Sawitri; Ragheed Imam Rashaqa; Syari'ah Dinila Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The scarcity and escalation of fuel oil prices (BBM) have become economic issues that significantly affect national economic stability, particularly the Consumer Price Index (CPI). This research intends to examine the causes of fuel scarcity, the factors influencing fuel price increases, and their impact on CPI stability in Indonesia. The research employs a qualitative approach using a conceptual study through literature review methods. Data were gathered from different secondary references, such as academic articles, economics publications, and official publications applicable to the study topic. The findings indicate that fuel price increases are influenced by both external and internal factors, such as the Russia–Ukraine geopolitical conflict, rising global oil prices, the depreciation of the rupiah exchange rate, increasing fuel consumption, and the growing burden of government fuel subsidies on the state budget. The escalation of fuel prices directly impacts production and distribution costs, which subsequently triggers inflation through the cost-push inflation mechanism. These impacts lead to rising prices of basic necessities, declining public purchasing power, and worsening economic conditions for low-income communities. Furthermore, fuel price increases also contribute to CPI instability through rising inflation expectations within society. Therefore, appropriate government policies are needed through coordination between fiscal and monetary policies, targeted subsidy distribution, and the strengthening of the national energy sector in order to maintain price stability and public welfare.